DEVELOPMENT OF SYSTEM-BASED FEATURES FOR THE SPOOFED SPEECH DETECTION (SSD) TASK - 528, Ms.Mandeep Kaur, Mr. R.K. Sharma (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In order to determine system characteristics, we investigate the basic concept that speech is analysed by the human ear in subbands (due to the signal processing abstraction of the cochlea, i.e., vibration of basilar membrane in a specific region for a specific tone). Systembased features, such as the Sub band Auto encoder (SBAE) characteristic, which is an AE architecture modified to accommodate the human perception process, are employed in this article to recognise natural and faked speech. The Sub band Auto encoder (SBAE) function detects real and faked speech. It is an AE design that has been adapted to accommodate the human visual mechanism.